Surveillance of severe acute respiratory infections associated with SARS-CoV-2, influenza virus and RSV using ICD-10 codes: a case definition accuracy study across five European countries, 2021 to 2023 - Baltazar Nunes (Eurosurveillance, 2025)
BACKGROUND Surveillance of severe acute respiratory infections (SARI) using ICD-10 codes from electronic health records (EHR) lacks consensus on optimal case-defining codes. AIM We determined codes that maximise sensitivity (Se) and positive predictive value (PPV) for SARI associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza virus and respiratory syncytial virus (RSV) in Denmark, Iceland, Malta, Norway and Spain. METHODS We included hospitalisations from week 21/2021 to 39/2023, with ICD-10 diagnostic codes for respiratory disease (three-character codes J00–J99) or COVID-19 (U07.1, U07.2, country-specific codes for Denmark). We assessed Se and PPV of individual codes against laboratory results. Based on Se and PPV rank-sum, we selected the top 10 codes and combined them into 10 sets per pathogen. We identified sets that maximised the clinical utility index (CUI = Se × PPV), categorised as excellent (≥ 0.81), good (0.64–0.80), satisfactory (0.49–0.63) and poor (< 0.49). RESULTS We assessed 395,163 hospitalisations for SARI-SARS-CoV-2, 313,418 for SARI-influenza and 192,936 for SARI-RSV, all tested. For SARI-SARS-CoV-2, code U07.1 (B34.2A, B97.2A for Denmark) had excellent utility in Denmark, Malta, Norway, Spain (≥ 0.82), and good utility in Iceland (0.79). For SARI-influenza, J09, J10 and J11 performed excellently in Denmark, Norway, Spain (≥ 0.83), satisfactorily in Malta (0.52), and poorly in Iceland (0.43). For SARI-RSV, J12, J20 and J21 achieved highest CUI but had poor utility (0.17–0.34). CONCLUSIONS COVID-19- and influenza-specific three-character ICD-10 codes accurately identified SARI associated with SARS-CoV-2 and influenza virus. For SARI-RSV, four-character codes should be explored. We recommend context-specific assessments in countries adopting EHR-based surveillance.